von Willebrand factor as a biomarker of clinically significant portal hypertension and severe portal hypertension: a systematic review and meta-analysis - Chunqing Zhang; Ziyuan Zou; Xinwen Yan; Cheng Li; Xiaofeng Li; Xiaofen Ma; Shenghong Ju; Junzhang Tian; Xiaolong Qi (BMJ Open)
Objective This meta-analysis was performed to investigate the correlation between von Willebrand factor (vWF) antigen and hepatic venous pressure gradient (HVPG) and to evaluate the diagnostic performance of vWF to detect clinically significant portal hypertension (CSPH) and severe portal hypertension (SPH).Design Systematic review and meta-analysis.Methods MEDLINE, EMBASE, Web of Science and the Cochrane Library were screened up to 5 April 2018. Studies related to the diagnostic performance of vWF to detect CSPH and/or SPH with HVPG as the reference standard were included. Study quality was assessed by using the Quality Assessment of Diagnostic Accuracy Studies scale. Two authors independently used a standardised form to extract data.Outcomes The primary outcome was the correlation coefficient between vWF and HVPG. The secondary outcome was the diagnostic performance of vWF to detect CSPH or SPH.Results A total of six articles involving 994 patients were included in this study. Five of the included articles were used to stratify the results for the correlation coefficient, three for the diagnostic performance of CSPH and two for SPH. The pooled correlation coefficient based on the random effects model was 0.54 (95% CI 0.35 to 0.69), thus suggesting a moderate correlation between vWF and HVPG. The pooled sensitivity, specificity and area under the curve of vWF for CSPH detection were 82% (95% CI 78 to 86), 76% (95% CI 68 to 83) and 0.87 (95% CI 0.80 to 0.94), respectively. Regarding the ability of vWF to detect SPH, the pooled sensitivity and specificity were 86% (95% CI 80 to 90) and 75% (95% CI 66 to 83), respectively. These results supported the satisfactory diagnostic performance of vWF for CSPH and SPH detection.Conclusions vWF, as a novel biomarker, has a moderate correlation with HVPG and shows a satisfactory performance for the diagnosis of CSPH and SPH in patients with cirrhosis.